Access to information: Information disclosure in some South African organisations - R. Van Der Walt (South African Journal of Business Management, 2007)
Legislation such as the Labour Relations No 66 of 1995 and the Promotion of Access to Information Act No 2 of 2000 has paved the way for creation of a culture of un-coerced disclosure of information in South African organisations. The article reviews progress in respect of information disclosure in South Africa and other countries and discusses the effects of the LRA in regard to disclosure of information to trade unions and workplace forums. It then describes a study conducted by the author and discusses the findings. It concludes with pointing out certain weaknesses in the disclosure process and exhorts managements and the trade unions to work together to improve this important tool for achieving success in organisations and enhancing industrial democracy.
Keywords: 650